Evaluation of the prescription of antibiotics by endodontists in acute periapical abscess (Research, Society and Development, 2020)
This study aimed to evaluate the prescription of antibiotics in acute periapical abscesses by endodontists in the metropolitan region of Recife - PE. It was a cross-sectional, quantitative and descriptive study, with a sample of 100 endodontists, who worked in dentistry schools and private or public dental clinics. They answered a questionnaire on the prescription of systemic antibiotics in the treatment of acute periapical abscess and the data were analyzed descriptively using absolute and relative frequencies. Pearson's chi-square test or Fisher's exact test was used to evaluate the association between two categorical variables and the statistical program used was SPSS (Statistical Package for the Social Sciences) in version 23. The association of amoxicillin with potassium clavulanate in adult patients without penicillin allergy was prescribed by 50% of endodontists and in cases of penicillin allergy, clindamycin was the drug of choice with 67%. Most endodontists prescribed the antibiotic for 7 days. Regarding the prescription of antibiotics, most responded that they did not prescribe in all phases of the acute periapical abscess, however, when the evolutionary stages of this disease were determined, the results showed that there was a prescription in all phases, but with different percentages, being indicated when there was systemic involvement of the patient. It was concluded that the prescription of antibiotics by the endodontists surveyed was not consistent with the scientific literature, however, it showed a concern with the health and risk of serious systemic complications of the patient.